The Relevance of Ibnu Miskawaih’s Educational Thought to the Present Moral Education Curriculum - ANWAR, Saiful; TOBRONI (GNOSI: An Interdisciplinary Journal of Human Theory and Praxis, 2023)
The description of educational problems common in Indonesia, including the lack of professionalism of teachers or teaching staff, of course, must meet the competency standards of educators or several prerequisites that must be met. The welfare of educators is often disrupted, even though this is so important to support a good teaching and learning process. Better quality, then inadequate educational facilities and infrastructure in several places, such as areas that also affect the poor quality of learning. This condition also confirms that the large budget allocated for education in Indonesia is included in the 3T area or needs to be better organized. Education is synonymous with development, especially in the context of the national education system. Not only about the product of spatial layout and location but also the development of human resources. For example, what happens if a story in the education aspect does not accompany the growth in Indonesia? Even though it looks good physically, if the morality or morality of the subject in it is not good, then it is inevitable that problems will arise because of the lack of harmony. The rise of corruption cases in Indonesia, which predominantly involve public officials, is evidence of Indonesia’s lack of moral or moral development. Therefore, education should be a priority in the development of this country.